Evaluation of structure-activity relationship in novel metallophthalocyanines: Central atom effects on photophysicochemical and sonophotochemical singlet oxygen production - Kilicarslan, Fatma Aytan; Kutlu, Oznur Dulger; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
In recent years, photodynamic therapy (PDT) has emerged as a significant approach in cancer treatment, attributed to its selective cytotoxicity and minimal systemic toxicity. Nevertheless, its clinical application is constrained by limitations such as restricted light penetration, suboptimal therapeutic efficacy, and potential adverse effects on healthy tissues. To address these challenges, sonodynamic therapy (SDT) has been developed, offering advantages including greater penetration depth and reduced damage to surrounding tissues. Sonophotodynamic therapy (SPDT), which integrates the synergistic effects of both PDT and SDT, presents a more efficacious treatment strategy by enhancing the production of reactive oxygen species (ROS), particularly singlet oxygen (1O2), through the concurrent application of light and sound waves. In this context, phthalocyanine complexes are considered ideal candidates for SPDT applications, serving as both photosensitizers and sonosensitizers due to their structural modifiability, high photostability, and capacity for 1O2 production. This study involves the synthesis of Mg(II) (2), Zn(II) (3), and In(III) (4) phthalocyanine derivatives with naphthol groups carrying bromine atoms in non-peripheral positions, and a detailed investigation of the effects of substituent type and central metal on singlet oxygen yield using photochemical and sonophotochemical methods in DMSO. The single oxygen quantum yields obtained under photochemical excitation were determined to be 0.34 for 2, 0.77 for 3, and 0.85 for 4. Sono-photochemical excitation increased the singlet oxygen quantum yield by an average of 50% for 2, 3, and 4. This study has revealed the supportive effect of the excitation method on the production of singlet oxygen by synthesized compounds 2, 3, and 4, which play a significant role in the destruction of cancer cells. The findings contribute significantly to the development of new therapeutic agents with both light- and sound-sensitive properties, indicating that the synthesized complexes are promising candidates for future sonophotosensitizer studies.
Keywords: Phthalocyanines; Photodynamic therapy; Sono-photodynamic therapy; Singlet oxygen; Sensitizer; SUBSTITUTED ZINC PHTHALOCYANINES; PHOTOCHEMICAL PROPERTIES; METAL-FREE; SONODYNAMIC THERAPY; AGGREGATION; PHOTOSENSITIZERS; DERIVATIVES; SENSITIZERS; EFFICACY; Chemistry; Crystallography